Analysis of the company’s logistics system - O. V. Babich; L. S. Mityushenko; D. I. Selezneva (Путеводитель предпринимателя)
World tendencies of global economic development testify to the development of the producer market, as a result of which development of logistics and logistics systems takes place. In the article the main stages of the analysis of the logistics system of a food industry enterprise are considered, the relative indicators of the logistic system analysis are presented.